2-Bromo-4-(3,4-dimethyl-5-phenyl-1,3-oxazolidin-2-yl)-6- methoxyphenol - Hariono, Maywan; Ngah, Nurziana; A. Wahab, Habibah; Abdul Rahim, Aisyah Saad (International Union of Crystallography, 2012)
In the title compound, C18H20BrNO3, the oxazolidine ring adopts an envelope conformation with the N atom at the flap position. The mean plane of oxazolidine ring makes dihedral angles of 82.96 (13) and 70.97 (12)°, respectively, with the phenyl and benzene rings. In the crystal, adjacent molecules are connected via O—HO and C—HO hydrogen bonds and C—Hπ interactions into a zigzag chain along the b axis.